ANALYSIS OF FEATURES AND GENERALIZATION OF THE EXPERIENCE OF VOCATIONAL EDUCATION TRAINING FOR THE OIL AND GAS INDUSTRY - Antonenko , N; Prokopenko, O (Problems of Engineer-Pedagogical Education, 2023)
The paper presents materials highlighting important and current problems of training masters of vocational education for the oil and gas industry in various aspects of scientific and educational activities. The relationship between the conditions of innovative development of the oil and gas industry and its personnel support is also covered in the paper. The requirements for employment of specialists in the oil and gas industry are analyzed, and it is shown how they are taken into account in the preparation of masters in the educational program “Professional Education (Oil and Gas)” of the second master’s level of higher education. The relevance of the development and implementation of the system of training educational personnel for the industry is also justified. The results of the analysis of the educational program are presented, and the experience of training students in accordance with this program at Ukrainian Engineering Pedagogics Academy is summarized. The structure and content of the educational program is analyzed. The features and uniqueness of the educational program are shown. It is demonstrated that the interests and suggestions of stakeholder groups were taken into account when formulating the goals and program outcomes of the educational program in the contexts of the industry and region specifics. The paper demonstrates that the goals and program results of the educational program reflect trends in the development of the specialty and the job market. It is also highlighted that the educational program allows achieving educational results that meet the requirements of the National Framework of qualifications and are defined by the standard of higher education. The mechanisms of forming an individual educational trajectory of higher education students according to the educational program are presented. The structural and logical scheme of the educational program is exhibited; its implementation in the educational process is justified. The paper analyzes the particularities of the development and implementation of the vocational education system for the oil and gas industry, formulates and summarizes the scientific and educational results that were obtained by the authors during the implementation of the project.